Bridging In-school and Out-of-school Learning: Formal, Non-Formal, and Informal Education - Eshach, Haim (Journal of Science Education and Technology, 2007)
The present paper thoroughly examines how one can effectively bridge in-school and out-of-school learning. The first part discusses the difficulty in defining out-of-school learning. It proposes to distinguish three types of learning: formal, informal, and non-formal. The second part raises the question of whether out-of-school learning should be dealt with in the in-school system, in view of the fact that we experience informal learning anyway as well as considering the disadvantages and difficulties teachers are confronted with when planning and carrying out scientific fieldtrips. The voices of the teachers, the students, and the non-formal institution staff are heard to provide insights into the problem. The third part discusses the cognitive and affective aspects of non-formal learning. The fourth part presents some models explaining scientific fieldtrip learning and based on those models, suggests a novel explanation. The fifth part offers some recommendations of how to bridge in and out-of-school learning. The paper closes with some practical ideas as to how one can bring the theory described in the paper into practice. It is hoped that this paper will provide educators with an insight so that they will be able to fully exploit the great potential that scientific field trips may offer.
Keywords: RLitt; ecb-lm; ish17